Methylsiloxanes in plasma from potentially exposed populations and an assessment of the associated inhalation exposure risk - Guo, J.; Y. Zhou; M. Sun; J. Cui; B. Zhang; J. Zhang (Environment International, 2020)
Methylsiloxanes (MSs) are ubiquitous in indoor air and pose an important health risk. Thus, assessments of indoor inhalation exposure by measuring MSs levels in plasma are needed. In this study, we measured plasma MSs concentrations and evaluated daily indoor inhalation exposure in potentially exposed populations, including residents of industrial areas, university campus, and residential areas, all located in southwestern China. The concentrations of MSs in indoor air (gas-phase and PM2.5) collected from factory housing and from girls’ dormitories on university campus were approximately one to three orders of magnitude higher than in parallel samples from other areas. The consequences of MSs exposure were investigated by measuring MSs levels in the plasma samples of the exposed populations. Relatively high levels of cyclic MSs (CMSs: D4–D6) were found in the plasma of the co-resident family members of factory workers and in female college students living in campus dormitories. The highest levels of CMSs (D4–D6) and linear MSs (L5–L16), 2.3 × 102 and 2.0 × 102 ng/mL, respectively, were detected in the very young (0–3 years old) co-resident children of factory workers. The average daily dose via inhalation (ADDinh) in different groups showed that the ADDinh values of all MSs (D4–D6, L5–L16) were one to two orders of magnitude higher in the co-resident family members of factory workers and in female college students than in other groups, indicating that both populations should be considered as potentially highly exposed to MSs. A further assessment showed that inhalation exposure is the main source of CMSs (D4–D6) in plasma for people exposed to high indoor air levels of these compounds. Although the health risk assessment showed that the health risk from inhalation exposure to D4 and D5 was acceptable for all of the studied groups based on the current chronic reference dose (cRfD), the maximum ADDinh,CMSs value in 0- to 3-year-old children was only 7.9-fold below the cRfD. Because the toxicity of other MSs is unknown, the potential health risk of MSs to very young children via inhalation exposure should be further analysed. © 2020 The Author(s)
Keywords: air pollutant; Air Pollutants; air pollution; air quality; ambient air; article; chemistry; Child; China; college student; concentration (composition); drug megadose; Environmental Monitoring; exposure; Female; Female college students; health; health hazard; health risk; Health risks; Housing; human; human tissue; Humans; Indoor; indoor air; indoor air pollution; Industrial area; Infant; Inhalation exposure; newborn; occupational exposure; Orders of magnitude; Parallel samples; plasma; Potential health risks; Preschool; preschool child; resident; residential area; Residential areas; residential location; Risk Assessment; School buildings; Silicon; siloxane; Siloxanes; Students; Three orders of magnitude; University campus; womens health; worker